Effect of different type of commercial npk fertilizer on height and biomass in ipomoea reptans / Athirah Mohd Elhamuddin - Mohd Elhamuddin, Athirah (Faculty of Applied Sciences, 2015)
The aim of this study is to measure the height and calculate the biomass of Ipomoea reptans. People are concern with the rationale of using chemical fertilizer over getting the benefits of higher growth yield and other physical measurement of the produce. The methods involved planting, fertilizing, and observation of heights, sample preparation and determination of Ipomoea reptans’s biomass. As a result, the application of commercial NPK fertilizer on Ipomoea reptans does not significantly (p>0.05) affect its height and biomass (AFDW) using ANOVA. Ipomoea reptans treated with NPK 5:5:5 fertilizers had the highest mean height on day 21 while the lowest was Ipomoea reptans with no treatment of NPK fertilizer (control). The second highest was Ipomoea reptans with NPK 12:12:17:Mg2:TE treatment, followed by Ipomoea reptans with NPK 15:15:15 treatment, then Ipomoea reptans with NPK 21:21:21 treatment while the second lowest was Ipomoea reptans with NPK 13:13:21 treatment. Furthermore, biomass of the stem, leaves, and roots part of the Ipomoea reptans range from 85% - 89% in content overall.